EVALUASI SISTEM INFORMASI AKUNTANSI PADA PROSEDUR PEMBELIAN BAHAN BAKU - Wulandari, Mei -; Kristianto, Djoko - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2012)
Abstract The purpose of this study was : 1) to determine whether the accounting information system has been applied to the purchase of raw materials by PT. Batik Danar Hadi of Surakarta, 2) In order to determine whether the systems and procedures for the purchase of raw materials applied PT. Batik Danar Hadi of Surakarta in accordance with the Internal Control System and procedures in terms of organization, system of authorization and recording procedures, and practices healthy. This research is a form of survey, the research carried out by studying and reviewing the situation or problem in a research object. In this study, the authors take an object of research at PT. Batik Danar Hadi of Surakarta. The type of data being used is qualitative data and quantitative data. Sources of data using primary data and secondary data. Data collection techniques used interviews, questionnaires, and documentation. Data analysis techniques with a qualitative descriptive analysis technique to compare theory with practice. The results of this study indicate that the accounting information system has been applied to the purchase of raw materials by PT. Batik Danar Hadi of Surakarta. Systems and procedures for the purchase of raw materials applied by PT. Batik Danar Hadi of Surakarta in accordance with the Internal Control System and procedures in terms of organization, system of authorization and recording procedures, and practices healthy. Keywords: Internal Control Systems, Procedures, Accounting Information Systems